Exploring Critical Listening Through LyricsTraining in EFL - Jefryan Syah Kurnia Putra; Deri Sis Nanda (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study explores students’ experiences in using LyricsTraining to support the development of critical listening in an English as a Foreign Language (EFL) context. The research was conducted during English Club activities at SMK Muhammadiyah Way Sulan, South Lampung, involving ten Grade X students. A qualitative descriptive design was employed to examine how students engaged with the listening activities. Data were collected through classroom observations across three sessions, semi-structured interviews, and a questionnaire. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that students experienced a gradual change in their listening behavior. In the early sessions, listening was dominated by word recognition and frequent audio replay. However, in later sessions, students began to demonstrate critical listening indicators such as claim identification, assumption awareness, tone interpretation, and questioning evidence. Although challenges related to fast tempo and pronunciation remained, students increasingly engaged in interpreting and evaluating the meaning of the lyrics. These findings suggest that LyricsTraining can support the gradual development of critical listening while helping learners manage listening difficulties in EFL learning environments.